2024
DOI: 10.1038/s41590-024-01745-9
|View full text |Cite
|
Sign up to set email alerts
|

Distinct ontogenetic lineages dictate cDC2 heterogeneity

Carlos M. Minutti,
Cécile Piot,
Mariana Pereira da Costa
et al.

Abstract: Conventional dendritic cells (cDCs) include functionally and phenotypically diverse populations, such as cDC1s and cDC2s. The latter population has been variously subdivided into Notch-dependent cDC2s, KLF4-dependent cDC2s, T-bet+ cDC2As and T-bet− cDC2Bs, but it is unclear how all these subtypes are interrelated and to what degree they represent cell states or cell subsets. All cDCs are derived from bone marrow progenitors called pre-cDCs, which circulate through the blood to colonize peripheral tissues. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…3c and d). These results suggest that the majority of lung cDC2s are in the same lineage, which is in agreement with a recent report demonstrating that the type B cDC2 (cDC2B) lineage is the dominant cDC2 population in the lung and that these cells descend from a common preDC2 progenitor 21 .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…3c and d). These results suggest that the majority of lung cDC2s are in the same lineage, which is in agreement with a recent report demonstrating that the type B cDC2 (cDC2B) lineage is the dominant cDC2 population in the lung and that these cells descend from a common preDC2 progenitor 21 .…”
Section: Resultssupporting
confidence: 93%
“…By contrast, mouse cDC2s are very heterogeneous, have low amounts of CD103 and display high levels of CD11b. The heterogeneity of cDC2s has confounded efforts to assign specific functions to these cells, but the advent of single cell RNA-sequencing (scRNA-seq) has provided some much needed clarity 18 , 19 , 20 , 21 . Our group recently reported that the cell surface marker CD301b (encoded by Mgl2 ) is present on the cell surface of most lung cDC2s at steady state 18 .…”
Section: Introductionmentioning
confidence: 99%